IMPLEMENTATION OF COMPETENCY-BASED CURRICULUM IN THE TAHFIDZ PROGRAM TO ACHIEVE A SUPERIOR AND COMPETITIVE MADRASAH - Thohir, Putri Fahmadia Dinda Maulida (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to evaluate and analyze the implementation of a competency-based curriculum in the Tahfidz program in an effort to achieve superior and competitive madrasas. The focus of this research covers two Islamic educational institutions, namely Madrasah Aliyah Nurul Jadid and Madrasah Tsanawiyah Nurul Jadid in Paiton Probolinggo. The research method used is a multi-case with a qualitative approach, involving data collection through interviews, observation and document analysis. The research results show that the implementation of a competency-based curriculum in the tahfidz program in both madrasas has had a positive impact on achieving the goals of superior and competitive madrasas. Evaluations are carried out on curriculum design, learning strategies and assessment methods to ensure that the tahfidz program does not only focus on memorization, but also on understanding and mastering the concepts of the Qur'an. In addition, it was found that support from stakeholders, availability of resources and the role of teachers in implementing the competency-based curriculum are important factors in the success of the tahfidz program. This research contributes to the context of Islamic education curriculum development by emphasizing the importance of a competency-based approach in preparing a generation of Muslims who are qualified and able to compete in the global era.